2022
DOI: 10.1103/physrevb.105.094437
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion pinning by disk-shaped defects

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[70] Skyrmion dynamics is often sensitive to the skyrmion wall thickness. [72] Spin helix (stripe) evolves into skyrmion crystals and subsequently into the ferromagnetic state as an external magnetic field increases. [67,68,70,71] The featured size of magnetic skyrmions is comparable to λ .…”
Section: Magnetic Skyrmion Materialsmentioning
confidence: 99%
“…[70] Skyrmion dynamics is often sensitive to the skyrmion wall thickness. [72] Spin helix (stripe) evolves into skyrmion crystals and subsequently into the ferromagnetic state as an external magnetic field increases. [67,68,70,71] The featured size of magnetic skyrmions is comparable to λ .…”
Section: Magnetic Skyrmion Materialsmentioning
confidence: 99%
“…Magnetic skyrmion, 1-3 a particle-like spin structure usually stabilized by Dzyaloshinskii-Moriya (DM) interaction, 4,5 has attracted much interest because of its rich physics [6][7][8] and possible implementations in various devices such as skyrmion diodes, 9,10 skyrmion ratchets, 11 racetrack memories, 12 logic gates, [13][14][15][16] and nano-oscillators. [17][18][19][20][21][22][23][24][25][26][27][28] Among them, nanooscillators based on skyrmions in circular nanodisks have been heavily studied because their high-frequency motion can be easily used for microwave generators and/or detectors.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recently, Wang et al theoretically showed that skyrmions can be pinned by disk-shaped defects. [22] On the other hand, skyrmions tend to experience a transverse deflection from the intended path of the driving force, which is known as the skyrmion Hall effect (SkHE), owing to the transverse Magnus force associated with nonzero topological skyrmion charge. [23,24] Subsequently, several methods have been proposed to overcome or eliminate SkHE.…”
Section: Introductionmentioning
confidence: 99%